2018
DOI: 10.1038/s41598-018-33100-y
|View full text |Cite
|
Sign up to set email alerts
|

Caloric restriction promotes functional changes involving short-chain fatty acid biosynthesis in the rat gut microbiota

Abstract: Caloric restriction (CR) is known to promote health and longevity, likely via modification of the gut microbiota (GM). However, functional and metabolic changes induced in the GM during CR are still unidentified. Here, we investigated the short- and long-term effects of CR on the rat GM using a metaproteogenomic approach. We show that a switch from ad libitum (AL) low fat diet to CR in young rats is able to induce rapid and deep changes in their GM metaproteomic profile, related to a reduction of the Firmicute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 71 publications
6
32
0
Order By: Relevance
“…This suppression of methionine content is key to metformin‐induced longevity in C. elegans . On similar lines, several studies have shown that DR and exercise in different species significantly alter the host microbiome . It might be possible then that in addition to metformin, several other pro‐longevity interventions might exert their effect through microbial modulation of host mitochondrial dynamics and metabolism.…”
Section: Introductionmentioning
confidence: 92%
“…This suppression of methionine content is key to metformin‐induced longevity in C. elegans . On similar lines, several studies have shown that DR and exercise in different species significantly alter the host microbiome . It might be possible then that in addition to metformin, several other pro‐longevity interventions might exert their effect through microbial modulation of host mitochondrial dynamics and metabolism.…”
Section: Introductionmentioning
confidence: 92%
“…Likely, the beneficial effects of CR rely on multiple, highly connected intraand inter-cellular pathways. These include the modulation of genomic stability [43], counteraction of age-related epigenetic alterations [44], promotion of autophagy and of the optimal balance between protein synthesis and degradation [45], maintenance of the stem cells niche [46], regulation of tissue microenvironment [47] and of gut microbiota [48], amongst others.…”
Section: Discussionmentioning
confidence: 99%
“…The KRONA chart displaying the bacterial taxonomic groups at the phylum level organized by relative abundance suggested that compared to the red meat diet-fed animals, the fiber diet-supplemented groups (HF group denoted by blue nested sectors domain) showed a significantly increase in the proportion of Bacteroidetes (denoted by blue taxonomy nodes; Figure 2a), which could be attributed to the fact that Bacteroidetes are the main degraders of DF (Kaoutari, Armougom, Gordon, Raoult, & Henrissat, 2013;Schroeder & Bäckhed, 2016). In contrast, a high proportion of the phylum Firmicutes was observed in the gut microbiota of the RM group, which has been suggested to assist the host in efficient harvesting of calories compared with the Bacteroidetes group (Ash, 2007;Tanca et al, 2018). (Figure 2a).…”
Section: Diet-induced Changes In the Microbial Diversity And Composmentioning
confidence: 99%
“…mented groups (HF group denoted by blue nested sectors domain)showed a significantly increase in the proportion of Bacteroidetes (denoted by blue taxonomy nodes;Figure 2a), which could be attributed to the fact that Bacteroidetes are the main degraders of DF(Kaoutari, Armougom, Gordon, Raoult, & Henrissat, 2013;Schroeder & Bäckhed, 2016). In contrast, a high proportion of the phylum Firmicutes was observed in the gut microbiota of the RM group, which has been suggested to assist the host in efficient harvesting of calories compared with the Bacteroidetes group(Ash, 2007;Tanca et al, 2018).For example, RM-fed mice displayed a relatively high abundance of Chlamydiaceae, Lachnospiraceae, and Erysipelotrichaceae at the family level, when compared with other experimental groups (Chen et al, 2017; Radomski, Franzke, Matthiesen, Karger, & Knittler, 2019). Additionally, members of the Lachnospiraceae and Erysipelotrichaceae families have previously been suggested to be associated with microbe TMA generation and development of atherosclerosis (Qiu, Tao, Xiong, Yu, & Wei, 2018).…”
mentioning
confidence: 98%